Estuarine Fish Feeding Changes as Indicator to Mangrove Restoration Success in Seasonal Karstic Wetlands - Hernández-Mendoza, Lesli C.; Escalera-Vázquez, Luis; Arceo-Carranza, Daniel (Frontiers in Forests and Global Change, 2022)
The loss of mangrove areas due to anthropogenic activities has triggered efforts to recover or restore these ecosystems, their functions, and associated diversity. Such functions include nursery areas and energy flow through trophic relationships for a large variety of inhabitant species (e.g., fish). The food webs and trophic dynamics of estuarine fish provide important information on the food resources in mangrove ecosystems and their response to restoration processes. Nonetheless, few studies focus on using fish feeding characteristics as an approximation to assess the conservation or recovery status of these aquatic ecosystems. Thus, the aim of the present study was to compare the trophic dynamics of an ichthyic community in a mangrove ecosystem related to karstic wetlands in the Mexican–Caribbean using freshwater, estuarine, and marine fish species as bioindicators of the restoration process in mangroves. Stomach contents were analyzed for eight species of fish inhabiting specific mangrove zones (1—conserved zone, and 2—restored zone; a zone exposed to ecological restoration processes due to impacts of anthropic activities) related to karstic wetlands in the Mexican–Caribbean. Four feeding characteristics were considered: trophic guild, trophic level, feeding strategy, and prey abundance. Results showed differences and changes in the use of food sources at the trophic level mainly for Floridichthys polyommus, changing from a secondary consumer in the conserved zones to a primary consumer in the restored zones. This suggests that the feeding characteristics of the inhabiting fish are related to the mangrove’s conservation/restoration status and the trophic dynamics in the community. The results of this study are relevant as a tool for mangrove restoration plans regarding the analysis of fish and their food prey, in order to perform an easy and rapid assessment to determine the conservation/restoration status of these aquatic ecosystems from a functional perspective.